Real-life analysis of pathologic complete response with neoadjuvant trastuzumab plus taxane with or without pertuzumab therapy in HER2 positive locally-advanced breast cancer (HER2PATH Study) - Bilici, Ahmet; Ölmez, Ömer Fatih; Sezer, Ahmet; Öksüzoğlu, Berna; Kaplan, Muhammet Ali; Karadurmuş, Nuri; Çubukçu, Erdem; Şendur, Mehmet Ali Nahit; Aksoy, Sercan; Erdem, Dilek; Başaran, Gül; Çakar, Burcu; et al. (Lippincott Williams and Wilkins, 2022)
[Abstract Not Available]
Keywords: HER2PATH Study; Breast Cancer; Analysis of Pathologic